2013
DOI: 10.1186/1471-2164-14-179
|View full text |Cite
|
Sign up to set email alerts
|

miRConnect 2.0: identification of oncogenic, antagonistic miRNA families in three human cancers

Abstract: BackgroundBased on their function in cancer micro(mi)RNAs are often grouped as either tumor suppressors or oncogenes. However, miRNAs regulate multiple tumor relevant signaling pathways raising the question whether two oncogenic miRNAs could be functional antagonists by promoting different steps in tumor progression. We recently developed a method to connect miRNAs to biological function by comparing miRNA and gene array expression data from the NCI60 cell lines without using miRNA target predictions (miRConne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 88 publications
(104 reference statements)
1
12
0
Order By: Relevance
“…3). These observations are consistent with our understanding that the expression of both the miR-106b/93/25 and miR-17-5p/18a/19a/20a/19b/92a clusters is suppressed by p53 through an indirect mechanism via inhibition of E2F1 expression (44,47,48). Their up-regulation can then be attributed to the abilities of the HR HPV E6 to destabilize p53 and of the viral E7 to target the pRB/p130 protein family, resulting in the release of E2F from suppressive transcriptional complexes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3). These observations are consistent with our understanding that the expression of both the miR-106b/93/25 and miR-17-5p/18a/19a/20a/19b/92a clusters is suppressed by p53 through an indirect mechanism via inhibition of E2F1 expression (44,47,48). Their up-regulation can then be attributed to the abilities of the HR HPV E6 to destabilize p53 and of the viral E7 to target the pRB/p130 protein family, resulting in the release of E2F from suppressive transcriptional complexes.…”
Section: Discussionsupporting
confidence: 92%
“…We note that miR-25, miR-27a, miR-92a, and miR-378 are oncogenic miRNAs and miR-16, miR-22, miR-29, and miR-100 are tumor-suppressive miRNAs (39)(40)(41)(42) and that they are modulated by p53, E2F, and c-Myc (25,(43)(44)(45). Although miR-16, miR-25, and miR-92a from three different miRNA clusters and noncluster miR-378 all had increased expression, the expression of the miR106b/93/25 cluster produced from MCM7 transcript (46) appears to be the most sensitive to oncogenic HPV infection, with increased expression in each of the three miRNAs from this cluster in all assays (Table 1).…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have shown that DROSHA RNase IIIB mutations result in global impairment of miRNA processing, with specific impairment in tumor-suppressing miRNAs [Rakheja et al, 2014]. We demonstrate that miRNAPG mutations are associated with down-regulation of all members of the miR-200 family (miR-200a, -200b, -200c, -141, and -429), which are key regulators of MET [Hua et al, 2013]. Reduction of miR-200 results in a mesenchymal, highly motile, and aggressive phenotype of cancer cells [Ceppi et al, 2014; Park et al, 2008; Ceppi et al, 2010].…”
Section: Discussionmentioning
confidence: 70%
“…Tumors with only SIX1/2 mutations (lacking miRNAPG mutations) and tumors with copy number loss of the miRNAPG loci without concomitant miRNAPG mutations did not cluster with the mutant tumors. Cluster 4 is characterized by decreased expression of the entire miR-200 family (miR-200a, -200b, -141, and -429) and miR-181b, all of which are involved in MET and stem cell maintenance [Hua et al, 2013; Ceppi et al, 2010; Park et al, 2008; Ceppi and Peter, 2014]. Decreased expression of the miR-200 family is predicted to reduce MYC and E2F expression [Hua et al, 2013], as was observed in our GSEA analysis of the miRNAPG-mutant tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation